The legal context of employment discrimination in Malaysia - Abdul Wahab, Harlida (IJCWED, 2018)
Discrimination may deprive people of their equal rights. In employment, discrimination causes people being denied of jobs, confined to certain occupations, offered with lower pay, refused the promotion and increment, and so on. Despite capabilities and abilities of performing the job, ‘physical appearance’ or other grounds such as sex, race and colour of skin are the attributes that taken into consideration when recruiting, hiring and offering the job which apparently unjust. This obviously creates barriers to employment. Therefore, promoting equality by eliminating various forms of discrimination is essential. Without the legislation outlawing employment discrimination in Malaysia and having agreed that equality and nondiscrimination is a universally accepted principle, this article addresses the issue of employment discrimination that has become rampant in Malaysia by deliberating the subject matter from the legal context. The author begins the discussion by defining employment discrimination so as to give an understanding to the scope of coverage and further presented the types of discrimination by looking at the other jurisdiction, particularly the United Kingdom with special reference given to her anti discrimination law namely Equality Act 2010. Taking this as a foundation, the analysis of employment discrimination in Malaysian is presented by analyzing the available reported cases. On top of that, some leading cases are being discussed. The author found out that even though Malaysia does not explicitly outlaw employment discrimination, the related case-laws and judicial decisions signified that the courts are prepared to hear the claims on the subject matter yet within a limited grounds. It is therefore recommended for the government, particularly the Ministry of Human Resource, to introduce a workplace anti discrimination policy or guideline in order to deal with the issue.